Analisis faktor-faktor yang mempengaruhi impor kedelai di Indonesia - Nadya Grace; Rahma Nurjanah; Candra Mustika (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
The purpose of the study was to find out how significant the contribution of soybean imports to the total imports of the food crop subsector and the effect of production, harvested area, exchange rate, and consumption on Indonesian soybean imports. The data used in this study is secondary data in the form of time series data for the period 2000-2016 derived from surveys that have been processed by the Central Statistics Agency of Jambi Province. The analytical method used is a descriptive and quantitative analysis using multiple linear regression analysis. The results showed that the contribution of soybean imports to the total imports of the food crop sub-sector in Indonesia experienced an increase, which fluctuated every year with an average of 24.87 percent. Based on the results of multiple linear analyses, it can be concluded that the factors that influence soybean imports in Indonesia are jointly controlled by the variables of soybean production, harvested area, exchange rate, and Indonesian soybean consumption. Meanwhile, simultaneously and partially, the soybean production and consumption variables have a positive and significant effect on Indonesian soybean imports. In contrast, the harvested area variable had a negative and significant impact, and the exchange rate had a negative and insignificant impact on Indonesian soybean imports. Keywords: Contribution, Import, Production, Harvest area, Exchange rate,